A narrative sequencing and mentalizing training for adults with autism: A pilot study - Bylemans, Tom; Heleven, Elien; Baetens, Kris; Deroost, Natacha; Baeken, Chris; Van Overwalle, Frank (Frontiers in Behavioral Neuroscience, 2022)
Adults diagnosed with autism experience difficulties with understanding the mental states of others, or themselves (mentalizing) and with adequately sequencing personal stories (narrative coherence). Given that the posterior cerebellum is implicated in both skills, as well as in the etiology of autism, we developed a narrative sequencing and mentalizing training for autistic adults. Participants with official autism diagnosis were randomly assigned to a Training group (n = 17) or a waiting-list Control group (n = 15). The Training group took part in six weekly sessions in groups of three participants lasting each about 60 minutes. During training, participants had to (re)tell stories from the perspective of the original storyteller and answer questions that required mentalizing. We found significant improvements in mentalizing about others' beliefs and in narrative coherence for the Training group compared to the Control group immediately after training compared to before the training. Almost all participants from the Training group expressed beneficial effects of the training on their mood and half of the participants reported positive effects on their self-confidence in social situations. All participants recommended the current training to others. Results are discussed in light of cerebellar theories on sequencing of social actions during mentalizing. Further improvements to the program are suggested. Our results highlight the potential clinical utility of adopting a neuroscience-informed approach to developing novel therapeutic interventions for autistic populations.